Le dernier refuge des gens compliqués : de l’intérêt des chiffres et des mathématiques en traduction - Nicolas Froeliger (MediAzioni)
Grounded in both the works of cognitive sciences scholars like Kahneman and Pinker and, above all, in real-life examples, this contribution strives to demonstrate how having recourse to mathematical reasoning can be a source of simplification for translators – at least in pragmatic translation, and more specifically in technical or specialized translation. Some may argue that this is not the obvious choice, yet I shall try to demonstrate the flaws of this argument. Starting from the assumption that the translation of mathematical elements should by no means be literal, I argue that numbers are not only a language (itself translatable into everyday language), but also an element of culture. It is also shown that, paradoxically, the universe to which mathematics invites us is essentially a relaxing one, among other things, because it invites us to reason in terms of categories. It thus reminds us that translators should never give up on understanding and that to understand, one must represent the translated phenomena in concrete terms. Only by so doing, we make ourselves understood. This raises anew the question of expertise in translation, of the linguistic nature or otherwise of this operation, of the relationship between the analog and the digital, which spurs us to include the numerical aspects of documents to be translated into our approach, and of the profile of current and future translators, at a time when machine translation is becoming almost universally prevalent.